PROFILE OF PATIENTS RECEIVING TOTAL KNEE ARTHROPLASTY: A CROSS-SECTIONAL STUDY - BEZERRA, MARCELO JOSÉ CORTEZ (Acta Ortop Bras, 2017)
OBJECTIVE: To describe the epidemiological profile, presented deformities, associated comorbidities, and impact on quality of life in patients with knee osteoarthritis. This study was conducted in a philanthropic hospital in Fortaleza from 2014 to 2015. METHODS: Data were collected from medical records, epidemiological forms, and by applying the Lequesne index questionnaire, which contains several questions related to pain, discomfort and functional limitation to assess the severity of symptoms. RESULTS: Females were more prevalent (76.7%), as were patients over 65 years of age (61.6%) and non-whites (81.6%). As for comorbidities, 83.3% had hypertension and 31.7% had diabetes. Of the total, 76.5% cases were genu varum, and 23.5% genu valgum. According to the Lequesne index findings, 61.6% cases were “extremely severe,” and women had higher scores. CONCLUSION: Females were more prevalent and whites were less prevalent. The most frequent comorbidity was hypertension. Female and elderly patients have more severe disease according to Lequesne index score, and these findings were statistically significant. Level of Evidence II, Prospective Study.